2014
DOI: 10.1016/j.appet.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Implicit affective associations predict snack choice for those with low, but not high levels of eating disorder symptomatology

Abstract: OBJECTIVE The central purpose of the current study was to examine whether eating disorder symptomatology moderates the extent to which implicitly and explicitly measured affective associations with fruits, or the feelings and emotions individuals associate with them, predict food choice. METHOD Participants (N=107) completed both implicit and explicit measures of affective associations with fruits, a self-report of eating disorder symptomatology, and their cognitive beliefs about fruits. In a subsequent snac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Once again, we found that the two groups differed in their automatic hunger responses to healthy and unhealthy foods, and that of healthy (e.g., fruit) and unhealthy (e.g., candy) foods predict whether people will purchase or consume the former over the latter (Ellis, Kiviniemi, & Cook-Cottone, 2014;Prestwich, Hurling & Baker, 2011) as well as their likelihood of gaining weight across a one year period (Nederkoorn et al, 2010). Despite such findings, no published study has examined whether automatic food-related responses represent a useful determinant of food intake in clinical populations.…”
Section: Discussionmentioning
confidence: 67%
“…Once again, we found that the two groups differed in their automatic hunger responses to healthy and unhealthy foods, and that of healthy (e.g., fruit) and unhealthy (e.g., candy) foods predict whether people will purchase or consume the former over the latter (Ellis, Kiviniemi, & Cook-Cottone, 2014;Prestwich, Hurling & Baker, 2011) as well as their likelihood of gaining weight across a one year period (Nederkoorn et al, 2010). Despite such findings, no published study has examined whether automatic food-related responses represent a useful determinant of food intake in clinical populations.…”
Section: Discussionmentioning
confidence: 67%
“…Implicit biases predict food choice when individuals have a low cognitive capacity (e.g., being distracted or emotional after watching an upsetting film) or when there is low inhibitory control (e.g., high levels of impulsivity) [11,65,66]. Low inhibitory control heightens the impact of implicit food biases on overeating [67][68][69] and is associated with the ingestion of higher amounts of high-calorie food [70,71] the failure of diets [72], and even with obesity [70,[73][74][75][76]. Other authors found that implicit affective bias was a significant predictor of snack choice at low, but not high levels of ED symptomatology [76].…”
Section: Discussionmentioning
confidence: 99%
“…Low inhibitory control heightens the impact of implicit food biases on overeating [67][68][69] and is associated with the ingestion of higher amounts of high-calorie food [70,71] the failure of diets [72], and even with obesity [70,[73][74][75][76]. Other authors found that implicit affective bias was a significant predictor of snack choice at low, but not high levels of ED symptomatology [76]. Given the prior inconsistencies in the strength of the relation between implicit bias and spontaneous eating behavior [64], the study by [76] suggests that ED symptomatology may moderate the strength of the relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed implicit affect toward eating, average body, and EDsymptom stimuli with the affect misattribution procedure (AMP; Payne, Cheng, Govorun, & Stewart, 2005). The AMP is a widely used tool for studying implicit cognition and has been used to study evaluations of food and bodies among those with and without AN (Spring & Bulik, 2014) and has also been used to predict eating behaviors (Ellis, Kiviniemi, & Cook-Cottone, 2014).…”
Section: Current Studymentioning
confidence: 99%